Resource management and quality of service in third generationwireless networks. - Dixit, S.
The third generation networks and services present opportunities to offer multimedia applications and services that meet end-to-end quality of service requirements. The key parts of the standards are already in place, and limited 3G services have already been turned on. While the evolution to 3G occurs, many operators will implement 2.5G interim solutions for a good period of time. We discuss the various evolution scenarios from the present 2G networks to 3G networks. Then we present the UMTS QoS architecture and its requirements, followed by a discussion on QoS in 3G air interfaces, radio access network, and core network
Keywords: 2G digital networks; 3G air interfaces; 3G networks; 3G services; CDMA; GSM; QoS requirements; TDMA; UMTS QoS architecture; Core network; Multimedia applications; Multimedia services; Quality of service; Radio access network; Resource management; Standards; Third generation wireless networks